2021
DOI: 10.1007/s00249-021-01536-2
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic and heterophilic cadherin bond rupture forces in homo- or hetero-cellular systems measured by AFM-based single-cell force spectroscopy

Abstract: Cadherins enable intercellular adherens junctions to withstand tensile forces in tissues, e.g. generated by intracellular actomyosin contraction. In-vitro single molecule force spectroscopy experiments can reveal cadherin–cadherin extracellular region binding dynamics such as bond formation and strength. However, characterization of cadherin-presenting cell homophilic and heterophilic binding in the proteins’ native conformational and functional states in living cells has rarely been done. Here, we used atomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…3 Geographical extent of the ARBRE-MOBIEU network membership in 2020, at the end of its funding by COST publications with multiple network members listed as authors. In addition, this special issue of the European Biophysics Journal includes a diversity of original research articles, describing for instance the secondary structure analysis of CueR (Balogh et al 2021), the characterisation of the complex formed between Fep1 and DNA (Miele et al 2021) the analysis of the Dps-DNA interaction in Marinobacter hydrocarbonoclasticus (Jacinto et al 2021), the characterisation of melanoma cell markers (Sobiepanek et al 2021), the single-molecule study of cadherin bond rupture forces (VijiBabu et al 2021), the study of a sulphur iron protein (Almeida et al 2021) and that of a manganese superoxide dismutase variant (Bonetta et al 2021). These are good examples of how the network is helping research groups enhance their understanding of biological systems through an improved use of biophysical approaches.…”
Section: Scientific Outputs Of the Mobieu Cost Actionmentioning
confidence: 99%
“…3 Geographical extent of the ARBRE-MOBIEU network membership in 2020, at the end of its funding by COST publications with multiple network members listed as authors. In addition, this special issue of the European Biophysics Journal includes a diversity of original research articles, describing for instance the secondary structure analysis of CueR (Balogh et al 2021), the characterisation of the complex formed between Fep1 and DNA (Miele et al 2021) the analysis of the Dps-DNA interaction in Marinobacter hydrocarbonoclasticus (Jacinto et al 2021), the characterisation of melanoma cell markers (Sobiepanek et al 2021), the single-molecule study of cadherin bond rupture forces (VijiBabu et al 2021), the study of a sulphur iron protein (Almeida et al 2021) and that of a manganese superoxide dismutase variant (Bonetta et al 2021). These are good examples of how the network is helping research groups enhance their understanding of biological systems through an improved use of biophysical approaches.…”
Section: Scientific Outputs Of the Mobieu Cost Actionmentioning
confidence: 99%
“…[15,17,18] Fichtner et al [18] found that the basic energy landscape of the homotypic E1-5 bond is governed by a wide potential (> 1 nm) and low off-rates (�10 À 4 s À 1 ). Recently, Radmacher and coworkers [19] investigated the rupture forces of homophilic and heterophilic bonds of N-(neural), OB-(osteoblast) and E-(epithelial) cadherins in living fibroblasts and epithelial cells using single-cell force spectroscopy (SCFS). They found that homotypic bonds are stronger than heterotypic ones.…”
Section: Introductionmentioning
confidence: 99%
“…14–18 In the context of biophysical investigations, many AFM-based force spectroscopy (FS) configurations can be found: 19 a single-cell probe approaching a substrate coated with proteins; 20–25 an ECM-mimicking probe approaching an adherent cell; 11,26–30 a single-cell probe approaching an adherent cell. 16,31,32 Both cell–cell and cell–ECM interactions can be investigated, through the direct measurement of weak (10–100 pN) interaction forces, which are mostly cadherin or integrin related, respectively. 33–37…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] In the context of biophysical investigations, many AFM-based force spectroscopy (FS) configurations can be found: 19 a single-cell probe approaching a substrate coated with proteins; [20][21][22][23][24][25] an ECM-mimicking probe approaching an adherent cell; 11,[26][27][28][29][30] a single-cell probe approaching an adherent cell. 16,31,32 Both cell-cell and cell-ECM interactions can be investigated, through the direct measurement of weak (10-100 pN) interaction forces, which are mostly cadherin or integrin related, respectively. [33][34][35][36][37] The main advantage of FS techniques using tips functionalised with single proteins 29,30,38 is the simplification of the complex cell-microenvironment interface, allowing us to study one specific molecular interaction at a time.…”
Section: Introductionmentioning
confidence: 99%